N addition introduced illicit competition to plants is the reason of the negative impacts on plant species diversity - Wenjing Li (Global Journal of Ecology - Peertechz Publications, 2020)
In a published paper in Oecologia, the authors found that mowing mitigates the negative impacts of N addition on plant species diversity. After reading the paper, their results gave me a chance to think the mechanism of nitrogen enrichment on biodiversity. The most fundamental reason of nitrogen addition decreasing biodiversity is it introduced illicit competition to different species. Maintenance of biodiversity is how many species can obtain living conditions in the certain ecosystem. All control experiments must pay attention to introducing illicit competition to different species.